Knowledge Sharing Strategy in Improving The Quality of Human Resources Based on Multi-Tasking - Kasman, Kasman (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to analyze and examine the knowledge-sharing strategy carried out by school principals in improving the quality of multi-tasking-based human resources in schools. This research uses a qualitative approach with a case study. Research data were obtained from interviews, observation, and documentation. The data analysis technique is carried out in stages, from data collection, reduction, data display, and drawing conclusions. The results showed that; knowledge sharing conducted by school principals in improving the quality of multi-tasking-based human resources in schools is implemented through; formation of mindsets for all school members, training and upgrading of existing resources, formation of knowledge sharing forums, supervision with the principle of continuous improvement. This research has implications for the importance of performance productivity displayed by all school members in order to be able to become a competitive and highly competitive school